Solubility and Dissolution Study of Salicylamide - Isadiartuti, Dewi; Widjaja, Bambang; Wijaya, Hendra; Ardhani Dwi Lestari, Maria Lucia (Berkala Ilmiah Kimia Farmasi, 2022)
Salicylamide belonged to the class of NSAIDs (non-steroidal anti-inflammatory drugs) which had analgesic and antipyretic effects similar to salicylic acetyl acid but were not converted to salicylic acid in the body. When used orally, salicylamide did not cause inflammation and bleeding in the stomach. Salicylamide was a weak acid compound (pKa 8,2) whose solubility was affected by the environmental pH. On oral administration, salicylamide passed through the digestive tract in the pH range of about 1,5 - 8,0. According to the Noyes-Whitney equation, drug dissolution was affected by its solubility. The aim of this study was to evaluate the relationship between the solubility and dissolution of salicylamide in several pH dissolution media. Solubility tests were carried out in dissolution media with pH 1,2, 4,5, and 6,5 with an ionic strength (µ) of 0,2 in a water bath at 37 ± 0,5 °C until a saturated solution was formed. The dissolution test was carried out in a dissolution media solution with the same pH as the solubility test, using a paddle type stirrer at 50 rpm at 37 ± 0,5 °C for 60 minutes. The level of dissolved salicylamide in the solubility test and dissolution test was determined using a spectrophotometer at λmax for each pH of the medium. Salicylamide solubility and dissolution efficiency values in 60 minutes (ED60) were analyzed by one-way ANOVA at α 0,05. The results showed that the solubility of salicylamide increased with increasing pH. Increasing the solubility of salicylamide increased its dissolution.Keywords: Salicylamide, Ph Effect, Solubility, Dissolution, Noyes-Whitney equation